PENGARUH KONSENTRASI GULA DAN AGAR-AGAR TERHADAP KUALITAS PRODUK PUDING LABU KUNING - Ruksanan, Ruksanan; Hastian, Hastian; Abubakar, Abubakar (Sultra Journal of Economic and Business, 2021)
The purpose of this research is to: 1). knowing the interaction of sugar and agar concentration on the quality of pumpkin pudding product. 2). Knowing the right concentration in mixing sugar and agar for pumpkin pudding. 3). Determine the effect of sugar concentration on the product quality of pumpkin pudding. 4). Determine which treatment has the best effect on the quality of pumpkin pudding products. The implementation of this research was carried out by the experimental method with two treatments using a completely randomized design, the results of which were analyzed to determine the levels of vitamin C, total sugar and organoleptic tests (color, taste and texture).The results of this study are as follows: 1). Interaction The treatment of sugar and agar concentrations on the pumpkin pudding product produced is very good and is needed to be developed, 2). The right concentration in mixing sugar and agar is the addition of 100 grams of sugar concentration and 30 grams of agar (G2A3), 3). The effect of sugar concentration and agar on the making of pumpkin pudding shows a very significant effect.